2013
DOI: 10.1007/s00213-013-3267-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and behavioral characterization of adolescent protein kinase C following high dose ethanol exposure

Abstract: Rationale Ethanol is commonly used and abused during adolescence. Although adolescents display differential behavioral responses to ethanol, the mechanisms by which this occurs are not known. The PKC pathway has been implicated in mediating many ethanol-related effects in adults, as well as GABAA receptor regulation. Objectives The present study was designed to characterize cortical PKC isoform and GABAA receptor subunit expression during adolescence relative to adults as well as assess PKC involvement in et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 68 publications
7
29
0
Order By: Relevance
“…More than likely, variations in other molecular pathways, such as other protein kinases, may contribute to the remaining gap in ethanol age-dependent hypnotic sensitivity. In support of this, our recent work indicating that cortical PKC activity also contributes to adolescent hypnotic responses further implicates the kinome in developmental ethanol-related behavior (Santerre, Gigante, Landin, & Werner, 2013). …”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…More than likely, variations in other molecular pathways, such as other protein kinases, may contribute to the remaining gap in ethanol age-dependent hypnotic sensitivity. In support of this, our recent work indicating that cortical PKC activity also contributes to adolescent hypnotic responses further implicates the kinome in developmental ethanol-related behavior (Santerre, Gigante, Landin, & Werner, 2013). …”
Section: Discussionsupporting
confidence: 61%
“…Although similar waking BECs between adolescents and adults have been noted (Silveri & Spear, 2002), other studies have reported age-related differences in BECs at waking (Broadwater, Varlinskaya, & Spear, 2011; Santerre et al, 2013; Silveri & Spear, 1998). The reasons behind this discrepancy are not clear, but work assessing ontogenetic ethanol metabolic rates in detail indicate that non-metabolic factors likely play a prominent role (Silveri & Spear, 2000).…”
Section: Discussionsupporting
confidence: 52%
“…This was shown by a decrease in their level of EtOH intake and BECs with a dose that did not significantly alter the consumption in adults, as well as by the longer duration of the effects induced by 16 mg/kg of THIP. These results could seem surprising, as lower levels of d-subunit have been reported in the adolescent brain (Laurie et al, 1992;Santerre et al, 2014). However, one might suggest that these receptors, despite their lower density, would be more sensitive to EtOH during adolescence, and thus would contribute more importantly to the modulation of alcohol drinking.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, each subunit exhibits a different developmental trajectory, suggesting that expression and function of GABA A receptors could modify over development (Henschel et al, 2008;Laurie et al, 1992). Interestingly, whereas the expression of c2 remains relatively constant, levels of d-subunit mRNA and protein increase over adolescence, with the highest levels found in adults (Laurie et al, 1992;Santerre et al, 2014). Due to the proposed involvement of d-containing GABA A receptors in the behavioral effects of EtOH, these modifications could contribute to age differences in alcohol consumption.…”
mentioning
confidence: 86%
“…The most notable developmental changes in GABA A receptor subunits have been reported for α 1 , α 2 , α 5 , β 2 , γ 2 , and δ subunits. In rodent and human studies, expression and regional distribution of the α 1 subunit is low at birth but is up-regulated during the early postnatal period, peaking from P21–28 and then declining by 20% to reach adult levels at P60 (Gambarana, Beattie, Rodriguez, & Siegel, 1991; Santerre, Gigante, Landin, & Werner, 2013). In contrast, the α 2 subunit is more widely distributed at birth and is either constant or declines until adulthood (Laurie, Wisden, & Seeburg, 1992), although α 2 subunits are replaced by α 1 subunits (Fritschy, Paysan, Enna, & Mohler, 1994).…”
Section: Setting the Stagementioning
confidence: 99%